Is the star-formation rate in z ∼ 6 quasars overestimated?. Issue 3 (12th November 2022) - Di Mascia, Fabio; Carniani, Stefano; Gallerani, Simona; Vito, Fabio; Pallottini, Andrea; Ferrara, Andrea; Valentini, Milena
ABSTRACT: The large total infrared (TIR) luminosities ( L TIR ; ≳10 12  L⊙ ) observed in z ∼ 6 quasars are generally converted into high star-formation rates (SFRs; $\gtrsim\!{10}^2~{\rm M}_{\odot }\, {\rm yr}^{-1}$ ) of their host galaxies. However, these estimates rely on the assumption that dust heating is dominated by stellar radiation, neglecting the contribution from the central active galactic nucleus (AGN). We test the validity of this assumption by combining cosmological hydrodynamic simulations with radiative transfer calculations. We find that, when AGN radiation is included in the simulations, the mass (luminosity)-weighted dust temperature in the host galaxies increases from T ≈ 50 K ( T ≈ 70 K) to T ≈ 80 K ( T ≈ 200 K), suggesting that AGN effectively heats the bulk of dust in the host galaxy. We compute the AGN-host galaxy SFR from the synthetic spectral energy distribution by using standard SFR – L TIR relations, and compare the results with the 'true' values in the simulations. We find that the SFR is overestimated by a factor of ≈3 (≳10) for AGN bolometric luminosities of L bol ≈ 10 12  L⊙ (≳10 13  L⊙ ), implying that the SFRs of z ∼ 6 quasars can be overestimated by over an order of magnitude.